Probabilistic power flow calculation considering electro-thermo-mechanical dynamics of overhead conductor. (December 2022) - Wang, Mengxia; Yin, Yimin; Yang, Ming; Han, Xueshan
Highlights: The electro-thermo-mechanical coupling power flow model is formulated. The calculation framework of the probabilistic power flow considering electro-thermo-mechanical dynamics (PPF-ETMD) is presented. The uncertainties of the meteorological conditions are considered in the calculation of PPF-ETMD. Two fast calculation methods are presented to improve the computation efficiency of PPF-ETMD. The distributions of the conductor temperature, stress and sag can be obtained by performing PPF-ETMD. Abstract: Conductor temperature and tension are important physical states that determine the security of the overhead line. The states are sensitive to the line power flow and the meteorological conditions around the conductor that have strong uncertainty. In this paper, the electro-thermo-mechanical coupling dynamics of the power system are modeled. Then, focusing on the calculation of the distributions of the electro-thermo-mechanical dynamics (ETMDs) of critical spans under the uncertain operational environment of the power system, the implementation framework and the fast calculation methods for the probabilistic power flow considering electro-thermo-mechanical dynamics (PPF-ETMD) are proposed. The work presented in this paper provides an effective method for operators to capture distributions of the ETMDs of critical spans under the uncertain environment and detect the underlying system security risk based on the thermal and mechanical essence of the security of the overhead line. Numerical simulations based on a regional power system in China and the IEEE 300-node system are carried out to verify the effectiveness of the proposed method.